Ammine Calcium and Strontium Borohydrides: Syntheses, Structures, and Properties - Jepsen, Lars H.; Lee, Young-Su; Cerny, Radovan; Sarusie, Ram S.; Cho, Young Whan; Besenbacher, Flemming; Jensen, Torben R. (WILEY-V C H VERLAG GMBH, 2015)
A new series of solvent- and halide-free ammine strontium metal borohydrides Sr(NH3)(n)(BH4)(2) (n=1, 2, and 4) and further investigations of Ca(NH3)(n)(BH4)(2) (n=1, 2, 4, and 6) are presented. Crystal structures have been determined by powder XRD and optimized by DFT calculations to evaluate the strength of the dihydrogen bonds. Sr(NH3)(BH4)(2) (Pbcn) and Sr(NH3)(2)(BH4)(2) (Pnc2) are layered structures, whereas M(NH3)(4)(BH4)(2) (M=Ca and Sr; P2(1)/c) are molecular structures connected by dihydrogen bonds. Both series of compounds release NH3 gas upon thermal treatment if the partial pressure of ammonia is low. Therefore, the strength of the dihydrogen bonds, the structure of the compounds, and the NH3/BH4- ratio for M(NH3)(n)(BH4)(m) have little influence on the composition of the released gasses. The composition of the released gas depends mainly on the thermal stability of the ammine metal borohydride and the corresponding metal borohydride.
Keywords: HYDROGEN STORAGE; THERMAL-DECOMPOSITION; METAL BOROHYDRIDES; CRYSTAL-STRUCTURE; X-RAY; COMPLEX HYDRIDES; AMMONIA; DEHYDROGENATION; PRESSURE; OCTAAMMONIATE